Cracking-resistance net-flow fingerprint scheme based on multi-dimensional orthogonal carriers - Cheng LEI; Hong-qi ZHANG; Yi SUN; Xue-hui DU (Tongxin xuebao)
Aimed at problems of unknown source identity, uncontrollable net-flow exchange and untraceable flow- ex-changing paths, it proposes cracking-resistance net-flow fingerprint scheme based on multi-dimensional orthogonal carri-ers. It uses two mutually orthogonal carriers so as to improve the capacity of fingerprint information. It achieves crack-ing-resistance by interval centroid carrier characteristics and hidden Markov model based decoding technique. Ultimately, it improves the robustness of scheme. What's more, it analyzes the resistance of multi-flow attack ability by using cen-troid attribute value to select embedding carriers randomly. Besides, it analyzes accuracy of fingerprint centroid algorithm and quantization index modulation decoding technique based on HMM under different cases. Finally, its invisibility and robustness is evaluated by experiments.